Similarity Index of Plankton in the Leachate Ponds at Gampong Jawa, Banda Aceh - Sri Rezki Ramadhani; M Ali Sarong; Ismul Huda (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2017)
Leachate is the liquid waste contaminated formed due to the influx of external water into the landfill, then rinsing and dissolving the materials on the landfill. Plankon is one of the bio-indicators that can be used to see the level of pollution a body of water. Plankton analysis has been done in laboratory from water that has been taken from leachate ponds at Gampong Jawa, Banda Aceh on August 2016. The aim of this research are to determine similarity index of Plankton. This research uses survey method and to take the sample using purposive random sampling method. Taking samples of plankton was done in three stations. The results were obtained seven species of phytoplankton that is Cymbella sp., Chroococcus sp., Denticula sp., Merismopedia sp., Mougeotia sp., Nitzschia sp., and Triceratium sp. Similarity index of plankton between 1st and 3rd station is 67%, 1st and 2nd station is 60% and 2 and and 3rd station is 60%. The similarity index value indicates that the degree of similarity in the leachate pond is high.Key Words: Similarity, Plankton, leachate ponds